Mobility of Time and Transportation in Deogracias A. Rosario’s "Greta Garbo" - Quilantang, Kimberly Nicole Panis (POETIKA, 2025)
This study examines Deogracias A. Rosario’s “Greta Garbo” through a symbolic and spatial-temporal analysis to explore the tensions of Filipino identity under American colonial influence. Employing a close textual reading method grounded in postcolonial theory—particularly Homi Bhabha’s concept of colonial mimicry and Michel Foucault’s notion of heterotopias—the research investigates how the narrative constructs and deconstructs identities shaped by modernization and Westernization. The protagonist, Monina Vargas, idolizes the Hollywood actress Greta Garbo and undertakes a train journey to meet her lover, Octavio Razon. This movement metaphorically embodies her oscillation between colonial illusion and disillusionment. The train functions not only as a literal vehicle of transportation but also as a metaphorical site of psychological transformation and cultural negotiation. Temporal markers such as the ticking clock and the train’s motion highlight Monina’s internal conflict, emphasizing the fleeting nature of her colonial aspirations. The study underscores the psychological displacement resulting from emulating foreign ideals by contextualizing spatial movement between Manila and Baguio (Bagyo) as a symbolic confrontation with colonial reality. Rosario’s use of the train and temporal motifs critiques the pervasive reach of Americanization in shaping Filipino consciousness, portraying the fragility of identities constructed on borrowed symbols. This analysis situates “Greta Garbo” within the broader discourse of Philippine literature during the American colonial period, illustrating how literature becomes a medium for articulating the contradictions of colonial modernity. Ultimately, the study contributes to ongoing conversations on mobility, cultural displacement, and identity formation in colonial and postcolonial contexts.